Investigation into transmission radiated noise during the acceleration of electric buses based on response surface methodology. (17th March 2021) - Chen, Yong; Qiu, Ningning; Zang, Libin; Wei, Changyin; Li, Guangxin; Li, Lin
The noise sources of 4-speed automated mechanical transmission of a pure electric bus are identified and optimised. The vehicle noise test under the acceleration condition is carried out. The results show that the 3rd-gear acceleration noise is more prominent than others. The transmission radiation noise model is established by using the boundary element method and revised by the noise test under the acceleration condition. The gear lead crown and involute modifications of the 3rd-gear pair are selected as design variables based on response surface methodology (RSM). The relationships between the design variables and the objective function are established. Finally, RSM is applied to optimise the transmission radiation noise transmission. The gear lead crown and involute modifications of shifting gears of the 3rd-gear were selected as -2 μm and 24 μm, respectively. The transmission measuring noise at the measuring point is reduced by 2-4 dB(A) on the 3rd-gear acceleration condition.